2009
DOI: 10.2528/pier09042104
|View full text |Cite
|
Sign up to set email alerts
|

Geometry Based Preconditioner for Radiation Problems Involving Wire and Surface Basis Functions

Abstract: Abstract-An innovative preconditioner has been developed in this work. It significantly improves the convergence of the iterative solvers applied to electromagnetic radiation problems by a renormalization of the matrix equation. The preconditioner balances the disparities in terms of magnitude and units caused by the strong self-coupling of the antennas, the non-uniformity of the meshes and also by the coexistence of wire and surface basis functions. It can be easily integrated into different electromagnetic s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Occasionally, some eigenvalues suddenly changes their sign (see later). Although the MoM code is based on the Galerkin testing procedure, the Z-matrix is not purely symmetrical [17]. As a result, some eigenvalues have unphysical imaginary parts which should be cut off.…”
Section: Eigenvaluesmentioning
confidence: 99%
“…Occasionally, some eigenvalues suddenly changes their sign (see later). Although the MoM code is based on the Galerkin testing procedure, the Z-matrix is not purely symmetrical [17]. As a result, some eigenvalues have unphysical imaginary parts which should be cut off.…”
Section: Eigenvaluesmentioning
confidence: 99%
“…Geometric preconditioners exploit additional information specific to the geometry of the underlying problem and can be more special-purpose. For example, it is reported that scaling with the edge lengths of RWG bases [23] is effective in the case of three-dimensional (3D) Maxwell equations [24].…”
Section: Introductionmentioning
confidence: 99%
“…Solving (1) by using MoM, the whole structure is discretized into small segments/triangles. J W and J S are then expanded by using the RWG basic functions defined on each pair of segments/triangles [13][14][15]. In this way, by using Galerkin testing method, we can obtain the following linear equations…”
Section: Modeling Of the Transceiversmentioning
confidence: 99%